2022
DOI: 10.48550/arxiv.2205.14171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lamellar fluctuations melt ferroelectricity

Abstract: We consider a Ginzburg-Landau theory for a ferroelectric phase transition whose primary order parameter (electrical polarization) is coupled to gradients of elastic strain (flexoelectricity). At the harmonic level, such couplings lead to a hybridization of acoustic and optic phonon modes and can lead to phases with modulated lattice structures that precede the symmetry broken state due to level repulsion [1][2][3][4][5]. Here, we show that at the mean field plus Gaussian approximation, the fluctuations of pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Coupling between the electrons and the TO mode plays a key role in a number of theoretical scenarios [21,22,26]. We have shown that a hybridized TO -TA phonon mode is to be taken L140301-4 into account and may even change the understanding of the ground state of quantum paralectrics [59].…”
mentioning
confidence: 99%
“…Coupling between the electrons and the TO mode plays a key role in a number of theoretical scenarios [21,22,26]. We have shown that a hybridized TO -TA phonon mode is to be taken L140301-4 into account and may even change the understanding of the ground state of quantum paralectrics [59].…”
mentioning
confidence: 99%